Legal Flaws in the Election of Wali Nanggroe 2018-2023 Period in Aceh - Muhammad Ihsan (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
The problem of elections in public office is often interesting to study, especially with the development of the electoral system which is continually being renewed to prevent corruption, collusion and nepotism, as well as to get candidates who are capable in their fields. One of these public offices which is Aceh-specific is Wali Nanggroe. This institution is a mandate of Aceh Government Law Number 11 of 2006. The determination of the Wali Nanggroe for the 2018-2023 period raises legal problems. Therefore this study will examine the wali nanggroe candidate selection system, the mechanism for selecting wali nanggroe based on Qanun number 8 of 2012, and whether there is a legal flaw in the election of wali nanggroe for the 2018-2023 period. This study uses a normative legal research method with a Law and Conceptual approach. The results of the research show that the wali nanggroe candidate selection system has not been carried out openly and transparently, even though Qanun allows for other candidates, in terms of election mechanisms, according to Qanun, an Election Commission must be formed in which there are 4 elements, but in practice the Commission Elections were not formed, this would be legally problematic, even legally flawed because one of the elements of the Election Commission was not involved as a member of the Election Commission as regulated by the Qanun. The elements that were not involved were representatives of ulama in each district/city.